Seroprevalence, infection, and personal protective equipment use among Colombian healthcare workers during the COVID-19 pandemic - Beltrán, Edgar O.; Martignon, Stefania; Coronel-Ruiz, Carolina; Velandia-Romero, Myriam L.; Romero-Sanchez, Consuelo; Avila, Viviana; Castellanos, Jaime E. (Frontiers in Public Health, 2023)
Introduction Healthcare workers (HCWs) are at the forefront of the COVID-19 response and frequently come into close contact with patients and their virus-contaminated body fluids. Recent studies have identified differential risks of infection and the use of personal protective equipment (PPE) among HCWs. However, available data might be interpreted with caution because of differences in the national health systems, local implementation issues, and adherence limitations to guidelines. A comprehensive description of infection, exposure at work, and biosafety habits during the COVID-19 pandemic has not been conducted among the HCW groups in Latin American populations. Objective To describe SARS-CoV-2 seroprevalence, infections, and extent of PPE use during the COVID-19 pandemic among HCWs at three different times, including dental practitioners (DP), nursing assistants (NA), physicians (P), and respiratory therapists (RT), from Bogotá, Colombia. Methods: After IRB approval, this cross-sectional study included 307 HCWs. Participants provided nasopharyngeal swabs and blood samples to detect viral RNA (RT-qPCR) and IgM/IgG anti-SARS-CoV-2 (ELFA-ELISA) at baseline (BL) and two follow-ups. Infection prevalence was defined as the number of positive-tested participants (RT-qPCR and/or IgM). Data on clinical status and biosafety habits were collected each time. Results Differential infection prevalence was found among HCWs through the study timeline (BL: RT-qPCR = 2.6%, IgM = 1.6%; follow-up 1 (45 days after BL): RT-qPCR = 4.5%, IgM = 3.9%; follow-up 2 (60 days after BL): RT-qPCR = 3.58%, IgM = 1.3%. Dental practitioners showed a higher infection frequency in BL and follow-up 1. IgG-positive tested HCWs percentage progressively increased from BL to follow-ups among the whole sample while index values decreased. Limitations in N95 availability and a high perception of occupational risk were reported. Conclusion A low prevalence of active SARS-CoV-2 infections among HCWs groups was found. Over time, there was an increase in participants showing IgG antibodies, although the levels of these antibodies in the blood decreased. Additionally, HCWs reported limitations in the availability of PPE as well as a variation in their safety practices.